Pengaruh Senam Lansia terhadap Hipertensi di Panti Sosial Rumoh Sejahtera Geunaseh Sayang Ulee Kareng Banda Aceh - Fauziah Fauziah; Ellyza Fazlylawati; Nur Afri Liandi Rasmin (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
Hypertension is one of the global public health issues with serious implications as it may lead to severe complications such as stroke, coronary heart disease, and kidney failure. Elderly individuals are among the most vulnerable groups, with the highest prevalence found in the age group of 65–74 years (57.6%) and those over 75 years (63.8%). Non-pharmacological treatment for hypertension includes regular and consistent elderly gymnastics. This study aims to examine the effect of elderly gymnastics on blood pressure among elderly individuals with hypertension at the Rumoh Sejahtera Geunaseh Sayang Nursing Home, Ulee Kareng, Banda Aceh. The study applied a quasi-experimental design with a deductive approach. The population consisted of 55 elderly individuals, and 17 were selected as the sample using total sampling technique. The elderly gymnastics intervention was conducted three times a week, from April 17th to 22nd, 2025. Blood pressure was measured before and after the intervention using a pre-test and post-test observation sheet. Data analysis was performed using the Wilcoxon test, suitable for non-parametric data. Results showed that on the first day, there was no significant difference in systolic and diastolic blood pressure (p = 0.091). On the second day, systolic blood pressure showed a significant decrease (p = 0.003), while diastolic pressure remained non-significant (p = 0.161). On the third session, a significant reduction occurred in both systolic (p = 0.000) and diastolic (p = 0.001) blood pressure. Conclusion: Elderly gymnastics has an effect on reducing blood pressure in elderly individuals with hypertension. This intervention may serve as an effective and applicable non-pharmacological therapy in daily life.